2006
DOI: 10.1590/s1413-70542006000400002
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biológicos da fase adulta de Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) oriunda de larvas alimentadas com Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae)

Abstract: RESUMOObjetivou-se estudar alguns aspectos biológicos da fase adulta de Chrysoperla externa (Hagen) quando as larvas desse predador foram alimentadas com ninfas e fêmeas adultas de Planococcus citri (Risso). O experimento foi conduzido em câmara climatizada regulada a 25 ± 1 o C, 70 ± 10% de UR e fotofase de 12 horas. Os adultos de C. externa cujas larvas foram alimentadas com ninfas nos três ínstares e fêmeas adultas da cochonilha, foram separados por sexo e 25 casais foram individualizados em gaiolas determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because of the predatory feeding habits, some lacewing species, e.g., the species of Chrysopidae, Hemerobiidae, and Coniopterygidae, are economically important and have been used for the biocontrol of agricultural pest insects (Goolsby et al 2000; McEwen et al 2001; Sato and Takada 2004; Bezerra et al 2006; Abdrabou 2008; Vidya et al 2010; Messelink et al 2016). However, the species identification of these lacewing groups is not easy to handle, particularly for people who are not the specialists of Neuroptera, because there are many morphologically similar species, which require examination of detail morphological characters, such as marking patterns on body and genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the predatory feeding habits, some lacewing species, e.g., the species of Chrysopidae, Hemerobiidae, and Coniopterygidae, are economically important and have been used for the biocontrol of agricultural pest insects (Goolsby et al 2000; McEwen et al 2001; Sato and Takada 2004; Bezerra et al 2006; Abdrabou 2008; Vidya et al 2010; Messelink et al 2016). However, the species identification of these lacewing groups is not easy to handle, particularly for people who are not the specialists of Neuroptera, because there are many morphologically similar species, which require examination of detail morphological characters, such as marking patterns on body and genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of some chrysopid species were observed to eat all developmental stages of P. citri (Bezerra et al, 2006). Although, the earlier reports demonstrated effective management of mealybugs with chrysopid larvae (Doutt and Hagen, 1949;Goolsby et al, 2000), these mealybugs may not be the most preferred and suitable prey for chrysopid larvae.…”
Section: Mealybugsmentioning
confidence: 97%
“…Lacewing larvae are potential candidates to apply to the so-called ''hot spots'' of mealybugs in greenhouse crops. Larvae of some lacewing species were shown to feed on all stages of citrus mealybugs (Bezerra et al 2006) and earlier studies showed promising control of mealybugs with green lacewing larvae Hagen 1949, 1950;Goolsby et al 2000). However, mealybugs may not be the most suitable and preferred prey of lacewing larvae.…”
Section: Introductionmentioning
confidence: 99%